Cord blood insulin, IGF‐I, IGF‐II, leptin, adiponectin and ghrelin, and their associations with insulin sensitivity, β‐cell function and adiposity in infancy. Issue 10 (31st May 2018) - Zhang, D. L.; Du, Q.; Djemli, A.; Julien, P.; Fraser, W. D.; Luo, Z. C.
Abstract: Aim: Vulnerability to insulin resistance and Type 2 diabetes may originate in early life, but little is known about whether any perinatal biomarkers are predictive of later metabolic health. We sought to assess whether cord blood insulin, insulin‐like growth factor (IGF)‐I, IGF‐II, leptin, adiponectin and ghrelin are associated with metabolic health indicators in infancy. Methods: In a prospective singleton birth cohort, we assessed cord blood insulin, IGF‐I, IGF‐II, leptin, adiponectin and ghrelin concentrations in relation to the homeostasis model assessment of insulin resistance (HOMA‐IR), β‐cell function (HOMA‐β), fasting proinsulin‐to‐insulin ratio, BMI z ‐score, and the sum of triceps and subscapular skinfold thickness (an indicator of adiposity) in infants at age 1 year ( n  = 185). Results: Adjusting for maternal and infant characteristics, one standard deviation (sd ) increase in cord blood adiponectin was associated with an 11.1% (95% confidence interval 1.8–19.5%) decrease in HOMA‐β ( P  = 0.02) and a 13.6% (1.8–26.8%) increase in proinsulin‐to‐insulin ratio ( P  = 0.02), indicating worse β‐cell function in infants at age 1 year. Onesd increase in cord blood insulin was associated with a 0.5 (0.1–1.0) mm increase in skinfold thickness ( P  = 0.01). Onesd increase in cord blood ghrelin was associated with a 0.2 (0.02–0.3) decrease in BMI z ‐score ( P  = 0.02) and a 0.5 (0.1–0.9) mm decrease ( P  = 0.02) in skinfold thickness. Cord blood IGF‐I and IGF‐II were not associated with the observed metabolic health indicators at age 1 year. Conclusion: The study is the first to show that cord blood adiponectin may be negatively predictive of β‐cell function, whereas cord blood ghrelin may be negatively predictive of adiposity in infancy. What's new?: The study is the first to show that cord blood adiponectin is negatively predictive of β‐cell function in infancy. Cord blood insulin‐like growth factor (IGF)‐I and IGF‐II appear not to be associated with insulin sensitivity, β‐cell function or adiposity in infancy.